Data Labels and Security Compliance in Public Tertiary Institutions in Rivers State, Nigeria - Chizi Ernuchi Obara (JOURNAL OF BUSINESS AND AFRICAN ECONOMY, 2026)
This study examined the extent to which data labels influence policy adherence and low incidents in public tertiary institutions in Rivers State, Nigeria. Grounded in the General Deterrence Theory and the Protection Motivation Theory, the study adopted a quantitative cross-sectional survey design. Data were obtained from 409 academic and non-teaching staff across five selected public tertiary institutions using a structured, validated questionnaire. Hypotheses were tested using simple regression analysis at a 0.05 level of significance. Descriptive statistics revealed grand mean scores of 4.12 for data labels, 4.18 for policy adherence, and 4.10 for low incidents, all exceeding the criterion mean of 3.0. Regression results showed that data labels significantly influenced policy adherence (β = 0.713, t = 18.442, p < 0.05, R² = 0.508) and low incidents (β = 0.668, t = 16.937, p < 0.05, R² = 0.446). These findings suggest that structured and consistently applied data labelling systems constitute a critical institutional mechanism for strengthening security compliance and reducing information security incidents in public tertiary institutions. The study recommends that institutional administrators formalise and enforce tiered data classification frameworks aligned with regulatory standards, particularly the Nigeria Data Protection Regulation.